2000
DOI: 10.1093/ps/79.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Washing and Cryoprotectant Effects on Frozen Storage of Spent Hen Surimi

Abstract: Mince of 98-wk-old spent hens was washed two times with 0.1% NaCl. Portions of unwashed and washed mince were mixed with a cryoprotectant (CP) composed of 4% sucrose, 4% sorbitol, and 0.2% Na-tripolyphosphate and were immediately frozen and stored at -20 C. Mince without CP was run as control. Textural properties of the stored mince and surimi were measured at 1-mo intervals for 6 mo, after being thawed at 4 C overnight, ground with 3% NaCl, and heated at 90 C for 15 min. For freeze-thaw stability study, mince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
0
20
1
2
Order By: Relevance
“…In another study, it was reported that deformation was slightly higher in surimi than in only washed minces and that this parameter increased during storage. However, it failed to show any strong correlation with other parameters of texture (Nowsad et al, 2000) as observed here.…”
Section: Texture Analysiscontrasting
confidence: 59%
See 2 more Smart Citations
“…In another study, it was reported that deformation was slightly higher in surimi than in only washed minces and that this parameter increased during storage. However, it failed to show any strong correlation with other parameters of texture (Nowsad et al, 2000) as observed here.…”
Section: Texture Analysiscontrasting
confidence: 59%
“…Deformation is influenced mainly by protein quality (Nowsad et al, 2000) and generally a higher grade surimi has a higher breaking force and deformation (Kohyama, Sakai, Azuma, Mizuguchi, & Kimura, 2001). However, it was reported that deformation was independent of the gel strength and that there was no significant difference among samples for deformation of two different grades of blue whiting surimi (Kohyama et al, 2001) and in giant squid muscle using different gelling ingredients (Go´mez-Guille´n & Montero, 1997).…”
Section: Texture Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian terkait surimi dan surimi-like lebih banyak mengkaji pencucian dan krioprotektan (Nowsad et al, 2000), frekuensi pencucian (Mega, 2006a), dan frekuensi pencucian dan pH (Jin et al, 2007(Jin et al, , 2008(Jin et al, dan 2009. Kajian terhadap ukuran partikel daging saat dicuci belum dikaji.…”
Section: Pendahuluanunclassified
“…Currently, surimi and surimi seafoods are also produced and consumed in many countries (Manfield, 2003). The successful development of the fish surimi process and increasing market share of surimi-based seafoods throughout the world have led to studies aimed the use of red meat and poultry in surimi product to develop new products from chicken (Nowsad et al, 2000;Lee and Min, 2004), and sheep (Antonomanolaki et al, 1999). Reported studies have identified large variations in functional properties of myofibrillar proteins associated with muscle fiber types.…”
Section: Introductionmentioning
confidence: 99%